Influence of whole-body vibration and drop jump on the range of motion in the ankle joint and running parameters-A randomized crossover study - Ewertowska, Paulina; Zapadka, Bartosz Zbigniew; Głażewska, Marta; Poniatowski, Łukasz; Tuptanowski, Kacper; Ossowski, Zbigniew; Czaprowski, Dariusz; Krzysztofik, Michał (Physiotherapy research international, 2024)
BACKGROUND AND PURPOSE: Warm-up (WU) is a commonly practiced technique aimed at preparing athletes for physical activity. Although coaches and athletes consider WU essential, there is still an ongoing debate about its effectiveness. This might be due to the fact that WU procedures often rely on experiences rather than scientific research. During WU, athletes may pursue intermediate goals such as ensuring proper ranges of motion in joints, which seem crucial particularly for runners' ankle joints. Hence, the aim of this study was to evaluate influence of whole-body vibration (WBV), drop jump (DJ), and a combination of both (WBV + DJ) in terms of ankle dorsiflexion and running parameters among recreational runners. METHODS: Sixteen runners performed as a WU: five sets of 30 s calf raises without WBV (CTRL), five sets of 30 s calf raises during WBV, five sets of six DJ, five sets of 30 s calf raises during WBV followed by 6 DJ. Range of motion (ROM) of the ankle joint was measured in a prone position using an inclinometer for the soleus and gastrocnemius muscles, separately. Measurements were conducted before and after WU, and after a 3000 m run. RESULTS: There was no interaction for time and WU for left (p = 0.926) and right (p = 0.738) soleus muscle as well as for left (p = 0.748) and right (p = 0.197) gastrocnemius muscles. No difference (p = 0.914) for the running time was found. DISCUSSION: WBV, drop jumps, or a combination of both did not affect ankle dorsiflexion and running time.
Keywords: dospělí; kosterní svaly; Female; klinické křížové studie; Adult; vibrace; mladý dospělý; ženské pohlaví; Warm-Up Exercise; běh; lidé; Cross-Over Studies; Muscle, Skeletal; Vibration; Running; Range of Motion, Articular; rozsah kloubních pohybů; Male; Young Adult; zahřívací cvičení; Ankle Joint; mužské pohlaví; hlezenní kloub; Humans